ULK1 gene polymorphisms and severe tuberculosis in the Chinese Han population: a case-control study - Zhang, Juan; He, Jian-Qing (Frontiers in Medicine, 2025)
ObjectivesPolymorphisms in the uncoordinated 51-like kinase 1 (ULK1) gene are associated with susceptibility to multiple diseases, including neurodegenerative disorders and specific cancer types. In tuberculosis (TB) research, autophagy is recognized as an essential host mechanism against Mycobacterium tuberculosis (Mtb) infection. Consequently, functional variations in the ULK1 gene may affect autophagic efficiency, influencing the host immune response to Mtb and altering the severity of TB. This study aimed to investigate the association between ULK1 gene polymorphisms and severe TB within a Chinese Han population using a case–control study design.MethodsA case–control study was conducted, with patients diagnosed with mild TB as controls and those diagnosed with severe TB as cases. Peripheral blood samples were collected from all participants for genomic DNA extraction. Four tag single nucleotide polymorphisms (SNPs) within the ULK1 gene (rs9481, rs7138581, rs11616018, and rs1134574) were selected based on genotype data from the Han Chinese population in Beijing. The association between these SNPs and TB severity was analyzed. Additionally, clinical phenotype analysis was conducted for the loci associated with TB severity.ResultsThe minor allele G of the ULK1 gene SNP rs1134574 (A > G) was significantly associated with an increased risk of severe TB (ORa = 23.499, 95% CI = 7.339–75.249, Pa < 0.0001). However, no statistically significant difference was observed in genotype frequencies or genetic models at this locus between severe and mild TB groups. Clinical phenotype analysis identified 995 patients with the AA genotype, 136 patients with the AG genotype, and 6 patients with the GG genotype at rs1134574. Significant differences were observed among these genotypes regarding the proportion of patients experiencing night sweats (p = 0.045) and the percentage of neutrophils (p = 0.046).ConclusionThe polymorphism rs1134574 of the ULK1 gene is significantly associated with severe TB, and clinical phenotype variations exist among different genotypes at this locus. These findings suggest a potential correlation between ULK1 gene polymorphisms and the incidence of severe TB within the Chinese Han population.